A review of policies and regulations of green infrastructure establishment in Kuala Lumpur, Malaysia - Seng Yeo, Owen Thian; Mohd Yusof, Mohd Johari; Maruthaveeran, Sreetheran; Saito, Kei; Abu Kasim, Junainah (Universiti Putra Malaysia, 2023)
Kuala Lumpur (KL), a capital city of Malaysia has experienced significant development that has led to the fragmentation of urban green spaces. Even though green infrastructure (GI) may address the problem of green space fragmentation, there is a notable gap in the extent to which the existing policies and regulations support the development of GI in KL. Hence, a set of policies and regulations pertaining to GI patch and corridor establishment in KL is reviewed in this study. In total, 77 documents related to policies and regulations that might contribute to GI establishment spatially were studied using thematic analysis. Next, the identified GI elements were themed together based on policies and regulations. The outcomes revealed that most policies and regulations focused on patches with 15 categories, followed by corridors (three categories) and components (one category). A typology of Malaysia’s GI from the policies and regulations is prescribed in this study. The reported findings may catalyse GI planning and establishment in KL for a more sustainable future.